Efficient charge-transport in hybrid lead iodide perovskite solar cells1. Issue 38 (14th October 2015) - Zhao, Jinjin; Wang, Peng; Wei, Liyu; Liu, Zhenghao; Fang, Xueqian; Liu, Xianglin; Ren, Deliang; Mai, Yaohua
<x xml:space="preserve">Abstract</x> We demonstrate a controllable TiCl4 processing technique for mesoporous TiO2 films, which modifies to achieve a uniform and high-coverage perovskite absorber layer, improves their charge collection and injection rate and enhances the device performance.